THE RESEARCH OF REINFORCED CEMENT LINER FOR RECONSTRUCTION OF WATER SUPPLY AND SEWER PIPES - Makisha, Elena (Journal of Applied Engineering Science, 2022)
The research is focused on the investigation of the features of mortar liner reinforced with composite mesh, which may be one of the possible options in case of one possible method of trenchless reconstruction of water and sewer pipes. The research had two goals: to study the strength under static loading of a mortar liner reinforced with a composite mesh frame and to define the maximum depth of underground location of a coating element, which is of significant importance if a host pipe cannot bear external loads any longer. Within the research, two specimens of coating with the length of 1000 mm and diameter of 800 mm were tested. The compression results showed that for both specimens the loss of bearing capacity occurred to the fluidity of composite reinforcement under the load of approximately 30 kN. After the strength test, a calculation was made to evaluate the maximum depth of liner location in case if a host pipe fully exhaustits bearing capacity. The results of the calculation showed that the maximum height of the soil layer above the crown of a pipe is 2.8 to 3.2 m depending on the type and features of the soil.